The Usage of Mobile Applications as a Form of Virtual Communication with Patients - Pilarczyk , Bogna; Rogala , Anna (Studia Oeconomica Posnaniensia, 2017)
Contemporary communication processes are dominated by modern technologies, owing to which consumers have gained access to many sources of information, while their market position has been strengthened. Communication in the virtual sphere has become more important, and the information behaviours of individuals often take place on the Internet, and also in the area of health. At the same time, the self-healing trend is strengthening, as patients are looking for ways to make their physical and mental state independent of public health. They are more willing to reach for over-the-counter drugs, dietary supplements and solutions in the hope of obtaining health-related information, monitoring the body or helping to maintain good physical condition. They include mobile applications, with those created at the request of pharmaceutical companies. The main objective of this paper is an analysis of the virtual communication process with the patient on the pharmaceutical market, with particular emphasis on the role of mobile applications. The specificity of virtual communication in this industry will be discussed, as well as tools used for communication with patients and their significance in the process of the self-healing of individuals. The article is based on a critical review of literature, industry reports and solutions in the field of communication in virtual space, including mobile applications.